The garbage crisis , environmental migrants and ecological justice in Campania (Southern Italy) - Romina Amicolo (Fourth International Conference on Degrowth for Ecological Sustainability and Social Equity, 2014)
The garbage crisis in Campania, a region of the Southern Italy, is an example of human – made enviromental degradation, which determined a sudden drop in the health condition of local inhabitants, with a considerable increase in the number of deaths caused by cancer, respiratory illnesses, and also genetic malformations. Since the mid-1990s the Italian government declared the state of emergency for waste disposal in Campania. During a demonstration against the Giugliano thermovalorizor, a woman said: "Before people leave Naples and Campania, because of unemployment; today people leave Naples and Campania because of ecological disaster. They don't want to die"(28th of September 2013). «The contemporary garbage struggle reveals that the distribution of power among social groups affects not only their social relations, but also the ecology of the urban/rural enviroments and, ultimately, of the human bodies inhabiting them»( Armiero, 2008). This reference supports the thesis, developed in this chapter, that ecomigration can be related to human – made enviromental degradation.